Efektivitas Sistem Self Assessment dalam Pajak Penghasilan di Kantor Pelayanan Pajak Pratama Batu - Zaimah, Toyyibatuz (Fakultas Syariah, 2016)
In the implementation of this system of self assessment, Taxpayers entrusted to count, make their own calculation of tax payable, aftr that deposit and then report to the tax offi. Along with the development of legislation, then in 2013 the PP No. 46 Year 2013. With the passing of PP 46 Year 2013 is expected to provide facilities for the society of UKM that become taxpayers in calculating the amount of tax payable. In addition, to assist the role KPP Pratama Batu in the discipline the perpetrators of UKM Batu thus increasing compliance of the businesses of UKM in paying taxes. However, the regulation of negative response by the taxpayer UKM because it is considered highly detrimental to the taxpayer.Agree-Disagree that occurs between the government and the taxpayer had impacted negatively on the implementation of the regulation, so in this study will be assessed the fist, the implementation of the system of self assessment in income tax on KPP Pratama Batu. Second, the constraints faced KPP Pratama Batu in the implementation of self-assessment. Thrd, the implementation of self-assessment system is reviewed based on the principle of al-amanah and principle of ash-shidqu.